Role of consolidative stereotactic ablative radiotherapy in patients with oligometastatic non-small cell lung cancer - Ricardi, Umberto; Levra, Niccolò Giaj; Badellino, Serena; Alongi, Filippo (Journal of Thoracic Disease, 2017)
Oligometastatic non-small cell lung cancer (NSCLC), presenting with one to five synchronous or metachronous metastatic lesions, has recently been considered a distinct disease state (1). In this setting, three different clinical conditions can be identified: (I) de novo oligometastatic—patients with a synchronous diagnosis of primary and metastatic lesions naive from oncological treatments; (II) oligorecurrent—patients with a controlled primary tumor after loco-regional treatment but with new and limited metastatic sites; (III) oligoprogressive—patients with a limited metastatic progression during systemic therapy (one or few sites), but with a control of the primary tumor and most of metastatic disease (2).